Associations between male reproductive health and exposure to endocrine-disrupting chemicals. (August 2019) - Rodprasert, Wiwat; Main, Katharina M.; Toppari, Jorma; Virtanen, Helena E.
Abstract: The incidence of many male reproductive disorders, including cryptorchidism and testicular cancer has increased. Semen quality in several countries has declined. Exposure to endocrine-disrupting chemicals (EDCs) — both prenatal and postnatal — has been proposed to have a role in these trends based on experimental data and animal studies. There is epidemiological evidence for an association between prenatal exposure to EDCs and cryptorchidism, hypospadias, and decreased anogenital distance, as well as an association between an exposure to EDCs in adulthood and semen quality. However, some of these findings are inconsistent across studies. There is less evidence about the role of prenatal exposure to EDCs for semen quality, and only few studies have investigated the role of prenatal EDC exposure in testicular cancer occurrence. This is due to a lack of long-term follow-up studies linking prenatal exposures with male reproductive disorders in adulthood. More research is needed investigating the role of EDC exposure for male reproductive health, particularly long-term follow-up studies to assess the outcomes in adulthood.